A systematic review of gastritis as an immune-related adverse event in clinical interventions - Fei Su; Wen-Xuan Fan; Yan Zhang; Xiao-Ling Zhang; Yun-Yi Du; Wei-Ling Li; Wen-Qing Hu; Jun Zhao (Taylor & Francis Group, 2024)
Immune checkpoint inhibitors (ICIs) are crucial in cancer treatment, and the associated immune-related adverse events (irAEs) have garnered significant attention, yet reports on associated immune related gastritis are limited. The diagnosis of immune related gastritis remains predominantly exclusionary, meanwhile its management diverges significantly from that of conventional gastritis. Current guidelines lack standardized grading criteria, and substantial data from large-scale, tertiary clinical studies are absent, therefore we conducted a systematic review of Medline, Web of Science, and Embase databases, identifying 31 articles from 2017 to December 31, 2023, involving 258 patients. Clinical manifestations included epigastric pain (53.1%), mucosal erythema (56.1%), and lymphocyte infiltration (48.6%). Corticosteroid therapy was common (94.7%), with 86.7% experiencing post-treatment improvement. 80% of patients can be diagnosed through endoscopy and pathology, while the remaining 20% may require PET-CT. Hormonal therapy is favored but diverges from standard management. Accurate diagnosis is crucial in managing immune related gastritis effectively.